(untitled) (Sains Humanika, 2017)
The purpose of this phenomenological study was to explore the experiences and perceptions of students who successfully completed their service learning projects in UTM. The qualitative approach was using and four main themes are emerged from the students interview, such as pedagogical aspect, personal benefits, challenges and problems. The findings showed that service learning has great implication and beneficial for students and community and develop soft skills for their career benefits.